Construção de uma biblioteca genômica de DNA para o camarão pitu Macrobrachium carcinus (Linnaeus, 1758), enriquecida para microssatélite - NOGUEIRA, Marcus Vinícius da Fonseca (2011)
The painted river prawn (Macrobrachium carcinus), occurs from Florida state (USA) to south Brazil. It is included in the red list of endangered species of the Brazilian Environmental Ministry. Restocking Programs have been used in the recovery of freshwater stocks. Such programs need to attend certain principles in order to assure that genetic diversity will be preserved. The knowledge on wild diversity and genetic structures is essential information to guide restocking activities. Microsatellite markers are frequently used to describe genetic structure because they are codominant, highly polymorphic and, selectively neutral. Total DNA was extracted, digested with RsaI enzyme, purified, dephosphorylated, and ligated to double-stranded linkers amplified via PCR. Hybridization used biotinylated probes for tetranucleotide (GACA)4 and (GATA)7 and trinucleotide mix (ATT)8, (CTT)8 and(GGT)8 motifs. DNA was linked into a cloning vector and transformed into competent cells Escherichia coli. A total of 358 clones were generated, being 237 positive clones, of which 161 were sequenced. Repetitive di (32), tri (7) and tetra (27) nucleotide were obtained and primers were designed using Primer3 software. Among optimized loci, six are monomorphic and 26 polymorphic. Most abundant repetitions are di (GA) n=14 and (TC) n=10, followed by tetra repetitions (GACA) n=8 and (TCGT) n=8, and (CTGT) n=7. A high number of tetranucleotides repeats are advantageous, since they can facilitate the process of allele discrimination, especially in poliacrylamide gel electrophoresis.